Seasonal Changes in Hydrogen Escape From Mars Through Analysis of HST Observations of the Martian Exosphere Near Perihelion. Issue 11 (22nd November 2017) - Bhattacharyya, D.; Clarke, J. T.; Chaufray, J. Y.; Mayyasi, M.; Bertaux, J. L.; Chaffin, M. S.; Schneider, N. M.; Villanueva, G. L.
Abstract: Hubble Space Telescope (HST) observations of the Martian hydrogen exosphere in Lyman α are presented in this paper for a period when Mars passed perihelion and southern summer solstice in its orbit. The peak intensity in the exospheric Lyman α brightness was recorded after Mars went past its perihelion, slightly after southern summer solstice. The increase in brightness as Mars approached perihelion was found to not be symmetric around the peak, making it impossible to fit the H escape flux trend with a single sinusoidal curve with the peak at perihelion. While the short‐term (~30 Earth days) changes were not directly correlated with changes in the solar Lyman α flux, the long‐term (~10 Earth years) trend in the data does show some correlation with solar activity. This suggests that the short‐term changes brought about in the exosphere could be due to intrinsic changes occurring within the lower atmosphere. For example, thermospheric heating by dust can alter the cold‐trapping mechanism for water vapor resulting in it being present in large quantities at higher altitudes (60–80 km), possibly enhancing the escape flux of H. Therefore, it is important to understand the drivers of atmospheric dynamics in the Martian atmosphere, which produce the yearly enhanced seasonal changes observed at Mars around periapsis and southern summer solstice in order to accurately determine the total amount of water lost over its history. Key Points: HST observations conducted as Mars passed perihelion and southern summer solstice Peak hydrogen escape flux detected at or after southern summer solstice Hydrogen escape dependent on solar activity, atmospheric dynamics, and velocity distribution of hot atoms